Analysis of White Mushroom Production in Eamo Center Ermera Municipality - Julio Souza Amaral; Martins, Leopoldino Vasco; Gomes, Armindo (International Journal of Integrative Sciences, 2024)
This study aims to determine the motivation of producers in the production of white oyster mushrooms (Pleurotus ostreatus), the investment costs of producers in their production and the input and output of the company in the production of oyster mushroomsThe methodology used in this practice is a descriptive analysis method such as direct observation to collect data in the field, interviews are a method of collecting data in the form of a list of questions according to systematics, documentation methods as data collection techniques. through primary data and the appointment of secondary data with documentation.Through the results of this practice, it can be seen that the income from the porcini mushroom business is positive for the development of the Fatuquero community, because EAMO can produce porcini mushrooms of six to ten thousand per serving with a market price of $ 0.85, so that each price multiplied by the number of mushrooms reaches seven to eight thousand. This shows that the annual income of $8,890.00, $7,788.55, $6258.55 from the total annual income of white mushrooms divided by the total production budget of $4,704.00 $3,456.00 $5,100.00 with a fixed cost of $8,201,010 activity 0 returns the R/C ratio of 6.087, 5.858, and 2.427 and this means that the R/C value is greater than >1 is a profitable tree breeding activity for the Fatuquero community which is a priority for development by EAMO